Clay and sawdust-based filters efficiency for the removal of dyes, chromium, and bacterial load: A promising approach for the treatment of industrial effluents - Mubashra Sadaqat; Abida Kausar; Munawar Iqbal; Fatimah M. Alzahrani; Mazhar Abbas; Wissem Mnif; Arif Nazir (Desalination and Water Treatment)
Water resources are increasingly being contaminated due to rapid industrialization and urbanization, and implementing effective wastewater treatment approaches is essential to address this issue. This work focuses on exploring the possibility of improving industrial water quality by utilizing clay filters synthesized from inexpensive material. Red clay, sawdust, sawdust ash, and calcium silicate were used for the preparation of filters. Different compositions of filters were optimized using two different industrial effluents, i.e., textile and tannery industry effluents. Filter B having an 80:20 ratio showed promising efficiency in enhancing the physiochemical parameters such as pH, total dissolved solids (TDS), conductivity and biological oxygen demand (BOD) of both effluents. Filter B also showed removed the bacterial load of wastewater effectively. The filter B removed dyes up to 75 % removal from textile effluent and 65.89 % of chromium from tannery effluent. The mineral composition, surface morphology and functionalities were determined using different techniques, namely XRD, SEM and FTIR of filter B. This study demonstrates that a red clay filter prepared using sawdust is highly efficient for the treatment of industrial effluents.